Faktor-faktor Yang Dianggap Sebagai Prediktor Terhadap Keefektifan Kelompok Tutorial Problem Based Learning (PBL) - Yani Istadi; Harsono Mardiwiyoto; Yayi Suryo Prabandari (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2012)
Background: The tutorial plays a central role in problem-based learning (PBL). The effectiveness of small group tutorials is one of the key aspects to the students’ success in exam. This study aimed to identify factors perceived as the predictors for effectiveness of PBL tutorial group.Method: The subjects of the study were all of the students (year of 2008) of the Medical College of Sultan Agung Islamic University who were taking tropical disease module. The adapted version of the scales adopted in this study included the scale developed by Van den Bossche et al. for assessing team effectiveness, beliefs about the interpersonal context and group’s learning behavior dimension, scale developed by Dolmans & Ginns for assessing tutor’s performance, scale developed by Munshi et al. for assessing quality of case problem, scale developed by Lepper et al. for assessing learning motivation. Quantitative approach with correlation and double regression analysis was applied.Results: The 223 subject included in the study consisting of 84 (37.3%) male and 139 (62.3%) female students. There was a significant correlation between effectiveness of tutorial group and a tutor’s performance (r = 0.456, p < 0.01), quality of case problem (r = 0.366, p < 0.01), beliefs about the interpersonal context dimension (r = 0.631, p < 0.01), group’s learning behavior (r = 0.559, p<0.01) and motivation (r = 0.137, p<0.05). There was a correlation between the variables of tutor’s performance, beliefs about the interpersonal context dimension, and learning behavior and group effectiveness indicated by the regression coefficient of 0.739 (p < 0.05). These three variables contributed to the group effectiveness as much as 54% with F value 87.857. The quality of case problem and motivations were not the predictive factors for group effectiveness.Conclusion: Improving tutorial group effectiveness requires improving factors beliefs about the interpersonal context dimension, group’s learning behaviors dimension and tutor’s performance. A favorable learning atmosphere is needed to improved motivation and better quality of case problem.